1993
DOI: 10.1002/aja.1001960202
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the border of the neural plate may be positioned by the interaction between signals that induce ventral and dorsal mesoderm

Abstract: In the early Xenopus. embryo, a quadrant of endodermal cells that have descended from the vegetal dorsal localization in the zygote produces signals that pass into the animal hemisphere and induce dorsal mesoderm from the marginal zone. From the remaining three quadrants of the bordering endoderm, signals pass into the animal hemisphere and induce ventral mesoderm in the marginal region. There is evidence that suggests that these same mesoderm-inducing signals continue through the plane of the tissue of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Grocott et al / Developmental Biology 370 (2012) 3-23 et al, 2003. Neural and non-neural transcripts continue to overlap in a broad territory, named 'the border' of the neural plate (Moury and Jacobson, 1989;Streit and Stern, 1999;Zhang and Jacobson, 1993), and it is in this region that precursors for neural, neural crest, placodes and epidermis are intermingled (Ezin et al, 2009;Fernandez-Garre et al, 2002;Garcia-Martinez et al, 1993;Hatada and Stern, 1994) and Irx1, one of the Six and Eya upstream regulators, is switched on under the influence of BMP and FGF signalling (Bellefroid et al, 1998;Glavic et al, 2002;Gomez-Skarmeta et al, 1998;Goriely et al, 1999;Khudyakov and Bronner-Fraser, 2009) (Figs. 2 and 3).…”
Section: Subdivision Of the Ectoderm By Sequential Activation Of Tranmentioning
confidence: 99%
“…Grocott et al / Developmental Biology 370 (2012) 3-23 et al, 2003. Neural and non-neural transcripts continue to overlap in a broad territory, named 'the border' of the neural plate (Moury and Jacobson, 1989;Streit and Stern, 1999;Zhang and Jacobson, 1993), and it is in this region that precursors for neural, neural crest, placodes and epidermis are intermingled (Ezin et al, 2009;Fernandez-Garre et al, 2002;Garcia-Martinez et al, 1993;Hatada and Stern, 1994) and Irx1, one of the Six and Eya upstream regulators, is switched on under the influence of BMP and FGF signalling (Bellefroid et al, 1998;Glavic et al, 2002;Gomez-Skarmeta et al, 1998;Goriely et al, 1999;Khudyakov and Bronner-Fraser, 2009) (Figs. 2 and 3).…”
Section: Subdivision Of the Ectoderm By Sequential Activation Of Tranmentioning
confidence: 99%
“…Xsna mRNA is a marker of a compartment that surrounds the neural plate from stage 11 in both the deep and superficial layers. In recognition of its precise differentiation from neighbouring tissues we designate it the neural plate border (also suggested by Zhang and Jacobson, 1993;Coffman et al, 1993). The boundaries of what will be within the closed neural tube is marked precisely in mid-gastrulae by the ventral edge of the superficial ectoderm border and the dorsal edge of the deep ectoderm border.…”
Section: The Neural Plate Bordermentioning
confidence: 99%
“…8A). In the other, Zhang and Jacobson, (1993) have shown using transplantation experiments that the position of the anterior neural plate border is determined by the relative strengths of two distinct signals emanating from the vegetal pole, one on the dorsal side with a neuralising effect and another on the ventral side which produces epidermis. Ectoder-ma1 Xsna is evidently a marker of an important element in this interaction.…”
Section: The Neural Plate Bordermentioning
confidence: 99%
“…Because this time precedes the morphological appearance and expression of molecular markers of neural folds and lateral primary neurons, neural crest cells and cranial placodes, Dlx activity is needed upstream of the process that induces these cell fates. Classical graft and extirpation experiments suggested that the anterior neural plate border is no longer susceptible to signals that reposition the border by late blastula stage (stage 9+) (Zhang and Jacobson, 1993). While the mediolateral border was not examined specifically, it is possible that these studies revealed the action of diffusible signals, such as BMP and Wnt, that bias ectodermal fates.…”
Section: Activity Regulates Cell Fates During Gastrulationmentioning
confidence: 99%